Sustainable Tourism: A Pathway To Responsible Travel and Environmental Conservation - Azamovna, Bakhromkulova Fotima (Journal of Ecotourism and Rural Planning, 2024)
This article explores the various aspects of sustainable tourism, benefits, challenges, and the role it plays in promoting a more sustainable future for the tourism sector. Through an analysis of sustainable tourism practices and strategies, this article aims to highlight the importance of embracing sustainability principles in the travel industry.